Implementation Of The Mapping System For Student Practical Work Locations Using Mobile Gis - Indra Pratistha; I Nyoman Alit Arsana; I Gede Iwan Sudipa (Institute of Computer Science (IOCS), 2022)
In the learning process, students in lectures do not only acquire theoretical material but students are also required to do practical work in companies. Practical work is intended so students can find out real problems in the field, increase knowledge and improve hard and soft skills. In its implementation, students can apply for practical work based on the choice of the location of the intended company, the system that has been running already accommodates the business process of applying for practical work. Still, there is no feature to find out the location distribution of practical work students. This study aims to utilize the API (application programming interface) on the Google Maps API and GPS (Global Positioning System) services to see the distribution of suitable work locations for INSTIKI students. The benefits of research to find suitable work locations for students at STIKI Indonesia are very important, considering that practical work is carried out in all regions in Indonesia, including remote areas. The application is built using mobile and web platforms to assist student users in submitting practical work data and coordinator users in monitoring the distribution of practical work students in several companies where practical work is located.